On Climate Fat Tails and Politics - Charles F. Mason; Neil A. Wilmot (Center for Economic Studies and ifo Institute (CESifo), 2023)
Transitioning the economy from one that relies on fossil fuels to one that emphasizes renewable energy sources will have important implications for the pattern of natural resource use. Such a transition depends on government policies. As elected politicians have an incentive to weigh the spatially heterogeneous costs and benefits on their constituents from taking political action, one might hope that particularly unusual climate events might provide an impetus to increased action. We undertake an analysis using a variety of data sources. We first investigate the stochastic process governing temperature anomalies allowing for "fat tails", which can arise either from a "jump" diffusion process or a time-varying volatility process. Using the parameter estimates from this first stage, combined with demographic and socio-economic variables, we analyze features promoting support for policies addressing climate change. Several of the parameter estimates that capture fat tails in temperature anomalies play a statistically important relation.
Keywords: Q20; D80; L15; 330; climate policy; temperature anomalies; fat tails; politics